Some Aspects of Regulatory Criteria for Metal-ligand Homeostasis in Epidermal Cells - V.I.Petukhov,; Е.V.Dmitriev,; L.Kh.Baumane,; A.V.Skalny,; Yu.N.Lobanova,; A.R.Grabeklis, (Journal of Antioxidant Activity, 2018)
The work is dedicated to the problem of the norm in the quantitative evaluation of metal content in the epidermal cells (hair) obtained by the method of spectrometry. Authors have analyzed the hair samples for Zn, Cu, and Fe content, which were obtained from 10000 healthy subjects (5000 males and 5000 females aged 20 to 45). The definition of the norm, in the authors’ opinion, is closely related to the basic positions of the theory of self-organized criticality (SC). The observed shifts in the homeostasis of essential metals are local and therefore cannot serve as a criterion of sufficient (or insufficient) metal content throughout the body.
Keywords: metal-ligand homeostasis; redox status; epidermis; self-organized criticality; oxidative/ nitrosative stress